1999
DOI: 10.1159/000015943
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular Reactivity Evaluated by Transcranial Doppler: Reproducibility of Different Methods

Abstract: Transcranial Doppler is routinely used to assess the cerebrovascular reactivity, despite scarce information on its reproducibility. We evaluated the reproducibility of cerebrovascular reactivity measurements by this method utilizing different vasodilatory and vasoconstrictor stimuli. The cerebrovascular reactivity was measured in 45 healthy volunteers during hypercapnia induced by inhalation of a mixture of 5% CO2 and 95% O2, breath holding and rebreathing, and during hypocapnia induced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
31
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 17 publications
7
31
2
Order By: Relevance
“…In that study we also proved that pCO 2 in capillary blood does not change significantly during the BH test, whereas pCO 2 significantly decreases after HV (arterial samples were not drawn as it was considered to be unethical in healthy volunteers). Previous studies reported on satisfactory reproducibility of both methods and a good agreement with other vasodilatory testing using different stimuli [29,30] .…”
Section: Discussionsupporting
confidence: 52%
“…In that study we also proved that pCO 2 in capillary blood does not change significantly during the BH test, whereas pCO 2 significantly decreases after HV (arterial samples were not drawn as it was considered to be unethical in healthy volunteers). Previous studies reported on satisfactory reproducibility of both methods and a good agreement with other vasodilatory testing using different stimuli [29,30] .…”
Section: Discussionsupporting
confidence: 52%
“…The reproducibility of model parameters and estimates of CVMR are comparable with other Doppler-CO2 tests (44,45,48). Nonetheless, the coefficient of variation of the model parameter b was relatively large compared with the other parameters ( Table 2).…”
supporting
confidence: 66%
“…In a previous study we proved that pCO 2 in capillary blood does not change significantly during the breath-holding test, whereas pCO 2 significantly decreases after HV (arterial samples were not drawn as it was considered to be unethical in healthy volunteers) [36] . Previous studies reported on satisfactory reproducibility of both methods and a good agreement with other vasodilatory testing using different stimuli [37,38] .…”
Section: Discussionsupporting
confidence: 52%
“…Therefore, changes in blood flow velocities measured by transcranial Doppler sonography during hypocapnia reflect the increase of the vascular tone at the level of the cerebral arterioles and are proportional to changes of cerebral blood flow in the territory of the assessed artery. A good short-and long-term reproducibility of the HV-induced cerebral vasoreactivity responses was demonstrated previously [27] and the method has been used in different conditions for assessing cerebrovascular reactivity [28][29][30] .…”
Section: Discussionmentioning
confidence: 55%